2015
DOI: 10.1111/nmo.12616
|View full text |Cite
|
Sign up to set email alerts
|

Targeting tachykinin receptors for the treatment of functional gastrointestinal disorders with a focus on irritable bowel syndrome

Abstract: This article reviews the literature concerning the role of TKs in the GI tract function in physiological and pathological conditions and their potential relevance in the treatment of functional GI disorders with particular reference to irritable bowel syndrome (IBS). The efficacy of NK1 antagonists in chemotherapy-induced and postoperative nausea and vomiting is well established. While pharmacodynamic studies have reported conflicting and negative results concerning the effects of NK1 and of NK3 antagonists, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 110 publications
(300 reference statements)
2
31
0
2
Order By: Relevance
“…In addition to the efficacy findings, ibodutant displayed an excellent safety and tolerance profile in the current and in previous studies 24. These trials showed no differences between treatments in the incidence rates for individual AEs, and SAEs were rare.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…In addition to the efficacy findings, ibodutant displayed an excellent safety and tolerance profile in the current and in previous studies 24. These trials showed no differences between treatments in the incidence rates for individual AEs, and SAEs were rare.…”
Section: Discussionsupporting
confidence: 66%
“…A previous study evaluated dose ranges between 10 and 60 mg daily in the overall IBS population, showing a statistically non-significant but consistent trend towards a higher response with the 10 mg dose in the IBS-D subgroup of patients, with no particular differences by gender, suggesting that males could not be completely unresponsive to ibodutant 24. In the present study, nevertheless, no significant effects were obtained in the male population, either using the EMA-specified or FDA-specified end points.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Blocking tachykinergic neurotransmission is a promising new approach for the treatment of IBS [65]. Ibodutant, a selective antagonist of the NK2 receptor with very low penetration in the brain, is currently being evaluated for women with IBS-D in phase III trials in European countries and in the United States [65]. …”
Section: Emerging Drugsmentioning
confidence: 99%